Autoimmune Disease in Women: Endocrine Transition and Risk Across the Lifespan - Desai, Maunil K.; Brinton, Roberta Diaz (Frontiers in Endocrinology, 2019)
Women have a higher incidence and prevalence of autoimmune diseases than men, and 85% or more patients of multiple autoimmune diseases are female. Women undergo sweeping endocrinological changes at least twice during their lifetime, puberty and menopause, with many women undergoing an additional transition: pregnancy, which may or may not be accompanied by breastfeeding. These endocrinological transitions exert significant effects on the immune system due to interactions between the hormonal milieu, innate and adaptive immune systems as well as pro- and anti-inflammatory cytokines, and thereby modulate the susceptibility of women to autoimmune diseases. Conversely, pre-existing autoimmune diseases themselves impact endocrine transitions. Concentration-dependent effects of estrogen on the immune system; the role of progesterone, androgens, leptin, oxytocin and prolactin; and the interplay between Th1 and Th2 immune responses together maintain a delicate balance between host defense, immunological tolerance and autoimmunity. In this review, multiple autoimmune diseases have been analyzed in the context of each of the three endocrinological transitions in women. We provide evidence from human epidemiological data and animal studies that endocrine transitions exert profound impact on the development of autoimmune diseases in women through complex mechanisms. Greater understanding of endocrine transitions and their role in autoimmune diseases could aid in prediction, prevention, and cures of these debilitating diseases in women.